City Logistics – A Complex, Yet Manageable System - Cvahte Ojsteršek, Tina (Strenghtening Supply Chains: Strategies for Resilience and Agility, 2026)
City (urban) logistics involves the management and optimization of distribution processes in urban areas, primarily focusing on the flow of goods, but occasionally also on people and information flows. In urban settings, freight traffic accounts for 10-15% of all distances travelled, causing issues such as congestion, environmental pollution, and road damage. Particularly, the activities of last-mile logistics in cities constitute a significant portion of transportation costs. Managing urban logistics involves various stakeholders, from city authorities, carriers, and merchants to residents and urban planners, all of whom play a crucial role in shaping and implementing effective urban logistic solutions. Solutions in this field can be categorized into soft measures, which focus on improving existing systems without major investments, and hard measures, which involve physical infrastructure changes and require more substantial investments. Some of the most vital measures include concepts like time windows, delivery points, parcel lockers, electric vehicles, consolidation centres, and even modern solutions such as crowdshipping. For smaller cities, which are common in Slovenia, these measures need to be adapted. National guidelines for the preparation of the Urban Logistics Management Plan were recently developed, laying the foundation for holistic and sustainable urban logistics in Slovenia.